2016
DOI: 10.17795/ijcp-4086
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of M30 and M65 Molecules in Transitional Cell Carcinoma of the Bladder and Their Relation to Tumor Progression

Abstract: BackgroundVarious markers are suggested for diagnosis and monitoring of transitional cell carcinoma of the bladder (TCC), including cytokeratins (CKs).ObjectivesIn the present study, the circulating CK18 (M65) and its caspase-cleaved form, ccCK18 (M30), have been investigated in a group of patients with TCC.Patients and MethodsSerum samples were obtained from 60 patients before surgical resection, among which the samples of 26 patients after resection were also included. We measured the levels of soluble M30 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous data have shown epithelial cell necrosis and apoptosis to be essential factors in the pathogenesis of various disease states, such as in acute liver injury or cancer . Bidirectional interactions between epithelial cells, fibroblasts, and interactions with matrix were also shown to play an important role in Idiopathic Pulmonary Fibrosis (IPF) pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown epithelial cell necrosis and apoptosis to be essential factors in the pathogenesis of various disease states, such as in acute liver injury or cancer . Bidirectional interactions between epithelial cells, fibroblasts, and interactions with matrix were also shown to play an important role in Idiopathic Pulmonary Fibrosis (IPF) pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have demonstrated and validated other non-invasive markers of liver status that were used in this investigation (M30-fragments) [45]. In addition, changes in recognized biochemical parameters, such us transaminases levels are the most common noninvasive methodology to assess fatty liver.…”
Section: Discussionmentioning
confidence: 81%
“…3 Bladder cancer is one of the most prevalent health issues in the world, with industrialized nations having the greatest incidence rates. [4][5][6] In the US, TCC ranks fourth among men's cancers and tenth among women's cancers, accounting for almost 95% of bladder malignancies. 7 The grading of cellular differentiation was used to classify the cellular morphology of TCC; well-differentiated cells were graded as 1, moderately-differentiated cells as grade 2, and poorly-differentiated cells as grade 3.…”
Section: Introductionmentioning
confidence: 99%